New insights in the molecular signature of advanced medullary thyroid cancer: evidence of a bad outcome of cases with double RET mutations. Issue 11 (28th July 2016) - Romei, Cristina; Casella, Francesca; Tacito, Alessia; Bottici, Valeria; Valerio, Laura; Viola, David; Cappagli, Virginia; Matrone, Antonio; Ciampi, Raffaele; Piaggi, Paolo; Ugolini, Clara; Torregrossa, Liborio; et al.
Abstract : Background: The RET proto-oncogene is responsible for the pathogenesis of hereditary (98%) and sporadic (40%) medullary thyroid carcinoma (MTC). In sporadic MTC, somatic RET mutations are associated with a poor prognosis. Objectives: We looked at the genetic profile of patients with advanced and metastatic MTC. The correlation between these mutations and outcome was also investigated. Methods: 70 patients with advanced and metastatic sporadic MTC were studied. Exons 10–11 and 13–16 of RET were analysed by direct sequencing. All cases were studied for RAS and the majority also for TERT mutations. RET/RAS -negative cases were analysed for other oncogene mutations. Results: 64/70 cases (91.4%) showed a somatic mutation, while 6 (8.6%) were negative. Among the mutated cases, RET mutations, mainly M918T, were the most prevalent (93.8%). K- or H-RAS mutations were present in 6.2% of cases and were mutually exclusive with RET. No other mutations were found. Four tumours showed two RET somatic mutations. We found a complex somatic RET alteration in 6/60 (10%) RET -positive sporadic MTC cases. A positive correlation between a poor prognosis and the multiple number of RET mutations was found. Conclusions: This study showed a high prevalence of somatic RET mutations in advanced and metastatic MTCs. RAS mutations were present in a small percentage of cases and mutually exclusive with RET mutations. In a small number of cases, more than one RET mutation was present in the same tissue. RET double mutations and, to a lesser extent, also complex mutations showed a worse outcome.